Influence of Mixture Composition Between Soybean Oil and Diesel Fuel on Characteristic of Droplets Combustion - Subagyo, Rachmat; Ansyah, Pathur Razi; Aminanto, Robbi Sholaiman (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
Depleting oil reserves has encouraged many researchers to search for new energy resources. Of many alternatives, soybean oil has been proposed as biodiesel. In this study, influence of mixture composition of soybean oil and diesel fuel on the droplet combustion characteristics was investigated. These characteristics included Ignition delay time, fire visualization, flame temperature and burning rate. The mixture comprises 10 to 50% soybean oil while the rest are Pertamina Dex diesel fuel. The study shows that flash point temperature, ignition delay time and burning rate increase as soybean oil content increases. In contrary, the flame height decreases with increasing soybean oil content.